Determinan Harga Saham Perusahaan LQ45 Berdasarkan Bukti Cross-Section pada Kondisi Makroekonomi Indonesia Tahun 2025 - Nindya Eka Sobita; M Iqbal Harori; Muhammad Mufti Hudani; Mega Mariska; Rizka Malia (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
This study aims to analyze the effect of company fundamental factors, proxied by Earning Per Share (EPS), Debt to Equity Ratio (DER), and Return on Equity (ROE), on the stock prices of companies listed in the LQ45 index on the Indonesia Stock Exchange. Indonesia's macroeconomic conditions, represented by the rupiah exchange rate and the BI Rate, are used as the economic context of the study and are not estimated as independent variables, since the study relies on a single-period cross-sectional dataset. This study employs cross-sectional data from 38 LQ45 companies as of December 2025 and was analyzed using the Ordinary Least Squares (OLS) method with EViews 13 software. The estimation results show that EPS has a positive and significant effect on stock prices, while DER and ROE have a negative and significant effect. The model explains 90.47% of the variation in stock prices (R² = 0.9047). These findings are consistent with signaling theory and capital structure theory, and have practical implications for investors in selecting stocks based on fundamental performance amid a relatively stable macroeconomic environment.